Cerebrospinal Analysis in Patients With COVID-19. (18th October 2020) - Miller, Emily Happy; Namale, Vivian S; Kim, Carla; Dugue, Rachelle; Waldrop, Greer; Ciryam, Prajwal; Chong, Alexander M; Zucker, Jason; Miller, Eliza C; Bain, Jennifer M; Willey, Joshua Z; Doyle, Kevin; et al.
Abstract: Background: Assessment of the impact of cerebrospinal fluid (CSF) analysis including investigation for the presence of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is essential for the optimization of patient care. Methods: In this case series, we review patients diagnosed with SARS-CoV-2 undergoing lumbar puncture (LP) admitted to Columbia University Irving Medical Center (New York, NY, USA) from March 1 to May 26, 2020. In a subset of patients, CSF SARS-CoV-2 quantitative reverse transcriptase polymerase chain reaction (qRT-PCR) testing is performed. Results: The average age of 27 patients who underwent LP with definitive SARS-CoV-2 (SD) was 37.5 (28.7) years. CSF profiles showed elevated white blood cell counts and protein in 44% and 52% of patients, respectively. LP results impacted treatment decisions in 10 (37%) patients, either by change of antibiotics, influence in disposition decision, or by providing an alternative diagnosis. CSF SARS-CoV-2 qRT-PCR was performed on 8 (30%) patients, with negative results in all samples. Conclusions: Among patients diagnosed with SARS-CoV-2, CSF results changed treatment decisions or disposition in over one-third of our patient cohort. CSF was frequently abnormal, though CSF SARS-CoV-2 qRT-PCR was negative in all samples. Further studies are required to define whether CSF SARS-CoV-2 testing is warranted in certain clinical contexts.